Hospital pharmacy workforce in Brazil - Thiago R. Santos; Jonathan Penm; André O. Baldoni; Lorena Rocha Ayres; Rebekah Moles; Cristina Sanches (BMC, 2018)
Abstract Background This study aims to describe the distribution of the hospital pharmacy workforce in Brazil. Methods Data were acquired, during 2016, through the Brazilian National Database of Healthcare Facilities (CNES). The following variables were extracted: hospital name, registry number, telephone, e-mail, state, type of institution, subtype, management nature, ownership, presence of research/teaching activities, complexity level, number of hospital beds, presence of pharmacists, number of pharmacists, pharmacist specialization. All statistical analyses were performed by IBM SPSS v.19. Results The number of hospitals with a complete registry in the national database was 4790. The majority were general hospitals (77.9%), managed by municipalities (66.1%), under public administration (44.0%), had no research/teaching activities (90.5%), classified as medium complexity (71.6%), and had no pharmacist in their team (50.6%). Furthermore, almost 60.0% of hospitals did not comply with the minimum recommendations of having a pharmacist per 50 hospital beds. The Southeast region had the highest prevalence of pharmacists, with 64.4% of hospitals having a pharmaceutical professional. This may have occurred as this region had the highest population to hospital ratio. Non-profit hospitals were more likely to have pharmacists compared to those under public administration and private hospitals. Conclusion This study mapped the hospital pharmacy workforce in Brazil, showing a higher prevalence of hospital pharmacists in the Southeast region, and in non-profit specialized hospitals.